Experimental cheap talk games: strategic complementarity and coordination - Jiménez-Jiménez, Francisca; Rodero-Cosano, Francisco Javier (Springer Nature, 2021)
This paper investigates experimentally the effects of communication in distinct games with complete information. We design four games resulting from the interaction between two incentive elements: strategic complementarity and coordination. These incentive elements allow to analyse the use of cheap talk as an efficiency-enhancing and coordinating device. We implement a restricted communication protocol (one-sided, optional, and closed-form) in repeated settings with fixed partners. Our findings provide robust evidence about how cheap talk interacts with incentives to explain strategic behaviour in a dynamic way. As expected, cheap talk increases efficiency under complementarity incentives, and the coordination level under coordination incentives. As novelty, the use of limited communication in repeated interactions has led to identify specific time-varying message profiles as the most effective messages in the coordination games. While the content of messages is explained by the complementarity incentives, faithfulness to credible messages is determined by the coordination incentives.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/16665
Keywords: Teoría de juegos; Cheap talk; Incentives; Strategic complementarity; Coordination